(untitled) (Global Journal of Science Frontier Research, 2018)
The smallholder tea sub-sector in Kenya has enjoyed relative growth in acreage output and number of growers since its inception in the early 1960s but productivity has remained low There are huge differentials between actual and potential yields suggesting underlying production inefficiencies This study estimated the level of technical efficiency and analyzed its determinants among tea farmers from two selected counties in Kenya Using data from a sample of 525 farm households the non-parametric data envelopment analysis was applied to estimate technical efficiency scores The scores were then regressed on a set of explanatory variables to establish their influence on efficiency The average efficiency score of 0 46 indicates that overall productivity in Kenya s smallholder tea sub-sector is low but has a potential to increase if most of the farmers can adopt practices of the frontier farms The intensity of family labor use farm size age of the tea farm education level of the household head access to extension services through the farmer field schools and the sale of green leaf through alternative marketing channels have a significant influence on levels of efficiency To exploit the existing potential for increasing productivity the smallholders should adopt labor saving technologies and replant to replace the aging tea farms Further government should implement actions to promote consolidation of small tea farms and expand the farmer field school extension programs to reach more farmers